Limited Attention as the Scarce Resource in an Information-rich Economy - Josef Falkinger (Institute for the Study of Labor (IZA), 2005)
This paper uses basic empirical facts from attention and perception psychology for a behavioral approach to equilibrium analysis at the industry and the macroeconomic level. The paper endogenously determines whether an economy is information-rich and whether scarcity of attention complements economic scarcity. A conventional economic equilibrium results if subjects have free attention capacity. At the positive level, the impacts of ITprogress, international integration and media on equilibrium diversity and level of attentionseeking activities are shown. At the normative level, welfare, efficiency and optimal policy interventions are characterized. Finally, behavioral effects of intensified attention-seeking on market power, sectoral economic structure and work-leisure choice are considered.
Keywords: D80; L10; D50; 330; limited attention; information-rich economies; media; diversity; behavioral equilibrium analysis